Feasibility of recovered toner powder as an integral pigment in concrete. Issue 1 (20th February 2019) - Newlands, Moray; Csetenyi, Laszlo; Zheng, Li
Abstract : Colour is an important property in many construction materials with pigments, coatings and paints being used primarily for aesthetic, safety and restoration purposes. However, the use of integral pigments in materials such as mortar and concrete can significantly increase material costs. Recovered toner powder (RTP) from printer and photocopier cartridges has the potential to be a low-cost and sustainable alternative pigment. The aim of this research was to examine the feasibility of using cyan, yellow, magenta and black RTP to create a range of colour options for mortar and concrete, and thereafter assess the colour stability in outdoor, indoor, ultraviolet and wet/dry conditions using the colour change parameter Δ E . The work showed that the RTP as a pigment could be blended to make a range of primary and secondary colours and had good colour stability in all environments with minimal impact on selected properties of hardened concrete.